Effects of weighted arm sleeve loading on golf shot parameters - Uthoff, A. M.; Lynn, S.; Neville, J.; Cronin, J. B. (The Journal of Sport and Exercise Science, 2021)
Golfing performance is dependent on the distance and trajectory of an athlete`s shot. The aim of this study was to determine how unilateral and bilateral loading strategies between 100-400 g placed on the forearms affected golf shot parameters related to carry distance and carry side distance. Nine experienced right-handed golfers, eight males (age: 24.5 ± 11.1 yrs; body mass: 84.8 ± 13.0 kg) and one female (age: 16.0 yrs; body mass: 73.6 kg), with an average handicap of 3.8 ± 2.6 performed golf shots with and without wearable resistance (WR) on their forearms. Unilateral loading on the lead arm resulted in increased carry distances from 1.68-1.78%, with 200 g loading significantly enhancing performance (p = 0.04; ES = 0.72). Unilateral loading of both 200 g and 400 g on the lead arm resulted in a large and very large change to carry side distance leading to a leftward ball trajectory (p = 0.02 and 0.01, respectively; ES = -2.07 and -4.43, respectively). No clear trends in individual performance were observed, apart from WR loading tending to cause a leftward carry side distance change back towards the target line in most of the subjects. These findings indicate that arm-loaded WR may be used to influence swing mechanics, which may assist ball carry trajectory in the desired direction, depending on a golfer`s individual abilities and needs.